The Architectural Genotype Approach in Contemporary Housing (1995 to 2010): The Case Study of Setif, Algeria - Rahmane, A.; Abbaoui, M. (Engineering, Technology & Applied Science Research, 2021)
The current paper aims to analyze the architectural genotype principle that considers the arrangement of spaces as an abstract relational model. The goal is to demonstrate that syntactic measurements show that spatial structures allow messages to be decoded in each dwelling’s inner spaces’ architecture. The research uses the justified graphic technique for spatial syntax. Twelve detached houses have been randomly selected out of a total of sixty-two contemporary buildings that were built in a subdivision of Setif between 1990 and 2010. The analysis findings showed that the spatial characteristics and properties that constitute the generic rule underlying the studied space can be detected. This research supports the notion that the implementation of the spatial syntax method can aid in the proposition of innovative solutions regarding the design of sustainable housing projects.